The BFG - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2019)
The BFG--Big Friendly Giant--kidnaps Sophie from her bed in the orphanage and takes her back to Giantland where she becomes involved in a scheme to end the loathsome activities of nine evil giants.
First published in 1982.
Ages 8-12.
Keywords: Giants (Folklore) -- Juvenile fiction; Orphans -- Juvenile fiction; Giants -- Fiction; Orphans -- Fiction; Giants; Orphans; Fiction; Juvenile works; Fiction; Fiction